"The screen shows movement – movement is interesting!" exploring effects of multimedia stories on preschool children's story comprehension and enjoyment. Issue 2 (17th June 2019) - Sung, Hui-Yun; Chen, Ssu-Han
Abstract : Purpose: Using multimedia and print storybooks, the purpose of this paper is to compare preschool children's reading engagement with and without adult support. Design/methodology/approach: A within-subject design is used to explore the effects of multimedia stories in supporting preschool children's story comprehension and reading enjoyment. A total of 24 children aged five to six years old from a local preschool in Taiwan participated in the experiments. Findings: A statistical analysis revealed the (non)differences in story comprehension between multimedia and print storybooks, with and without adult support. A content analysis revealed several important themes affecting children's reading enjoyment. These included multimedia elements (particularly motion and sound effects), haptic perception and the pause function. Research limitations/implications: Native Chinese speaking children participated in one-to-one sessions in Taiwan. To ascertain the generalizability of the findings presented in this study, further research is encouraged in other cultural contexts and settings. Practical implications: The paper provides insights into how multimedia and interactive features affect and enhance children's enjoyment. Recommendations are made to assist library professionals to incorporate digital media into children's programs. Originality/value: Children's reading motivation and engagement are often linked with improved reading attainments. This study elicited a range of perspectives and themes relating to what the children themselves felt influenced their enjoyment when reading print or multimedia storybooks. Findings were analyzed in a theoretical framework of facets of engagement.